2021
DOI: 10.1002/ange.202103253
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Superhelicenes: Easily Tunable, Chiral Nanographenes by Merging Helicity with Planar π Systems

Abstract: Incorporating helicity into large polycyclic aromatic hydrocarbons (PAHs) constitutes a new field of research at the interface between chemistry and material sciences. Lately, interest in the design of π-extended helicenes has surged. This new class of twisted, chiral nanographenes not only reveals unique characteristics but also finds its way into emerging applications such as spintronics. Insights into their structure-property relationships and on-demand tuning are scarce. To close these knowledge gaps, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…In both cases, no obvious signs of dimerization were found. For A three oxidation states at 0.9 V, 1.2 V, and 1.5 V could be identified, 26 while B showed oxidation at 1.0 V, and 1.3 V. 27 This is in line with the boundaries in which oxidation occurred in earlier ESI studies, [28][29][30] so that it seems perfectly reasonable to assume that the observed ions are the result of electrochemical oxidation inside the ESI source. The key experiment to further characterize the mixed doubly charged dimer ion is a so-called MS 2 experiment, in which the ion of interest is isolated from other ions and subjected to energyresolved collision-induced dissociations (ER-CID).…”
supporting
confidence: 79%
See 2 more Smart Citations
“…In both cases, no obvious signs of dimerization were found. For A three oxidation states at 0.9 V, 1.2 V, and 1.5 V could be identified, 26 while B showed oxidation at 1.0 V, and 1.3 V. 27 This is in line with the boundaries in which oxidation occurred in earlier ESI studies, [28][29][30] so that it seems perfectly reasonable to assume that the observed ions are the result of electrochemical oxidation inside the ESI source. The key experiment to further characterize the mixed doubly charged dimer ion is a so-called MS 2 experiment, in which the ion of interest is isolated from other ions and subjected to energyresolved collision-induced dissociations (ER-CID).…”
supporting
confidence: 79%
“…22 Following our earlier studies into the gasphase behaviour of hexabenzocoronene-substituted porphyrins, [23][24][25] the present study investigates the formation of radical cation dimers of the recently synthesized so-called superhelicenes. 26,27 These were identified as a fully-fledged family of p-extended helicenes with freely tunable physico-chemical characteristics and the prospect of further functionalization. Individual superhelicenes displayed remarkably high fluorescence quantum yields, while others showed absorption covering almost the entire visible region.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Moreover, the properties of these chiral structures can be further altered by incorporation of heteroatoms, such as nitrogen or oxygen. [8,9] For instance, substitution of one C(sp 2 )-H unit in an 8-membered ring with a nitrogen results in an azocine unit, which is formally antiaromatic according to Hückel, due to its 8 π-electrons. [10] To escape antiaromaticity, the azocine unit adopts a boat-like geometry.…”
Section: Introductionmentioning
confidence: 99%
“…37 The helical arrangement of NGs leads to inherently chiral PAHs, exhibiting strong Cotton effects and improved solubility compared to their flat analogues, such as those prepared by the groups of Wang, Martín, and Jux, among others. 34 35 38 In addition, their use as chiral dopants in emissive materials has been successfully demonstrated. 39…”
Section: Introductionmentioning
confidence: 99%